Identifikasi Telur Soil Transmitted Helminth (STH) Pada Kubis (Brassica oleracea) dan Kemangi (Ocimum basilicum) Di Penjual Makanan Sepanjang Jalan Dasa Darma Kecamatan Rawalumbu Kota Bekasi - Reza Anindita Anindita; Rosa Ihza Arlinda; Maulin Inggraini (Pendidikan Biologi,Universitas Islam Jember, 2022)
Worm infections caused by STH in Indonesia have a prevalence of 50%. One of the spread of STH occurs through soil or fertilizer contaminated with STH. If the soil or fertilizer contaminates vegetables, then the vegetables are potentially contaminated with STH eggs. If these vegetables are consumed by humans, they have the potential to cause diarrhea. This study aims to screen for the presence of STH eggs in vegetables commonly consumed by the public as fresh vegetables, namely cabbage (Brassica oleracea) and basil (Ocimum basilicum). This type of research is descriptive quantitative with cross sectional design. The samples in this study were 5 samples of basil and 5 samples of cabbage, each sample taken from 5 sellers of pecel catfish and grilled chicken along Dasa Darma street, Kec, Rawalumbu, Bekasi City. The sampling technique was done by purposive sampling. Data analysis was carried out with a quantitative descriptive approach. The results of this study showed that 5 samples of basil (100%) were positive for Hookworm eggs while all samples of cabbage were negative for Hookworm eggs. The conclusion of this study is that the use of the sedimentation method can be used as an early detection technique for the presence of Hookworm eggs in basil sold by pecel catfish and grilled chicken sellers along Dasa Darma street, Rawalumbu, Bekasi City. Keywords: STH, basil, cabbage, hookworm, sedimentation